THE EFFECT OF ABSCISIC ACID APPLICATION ON ROOT-SHOOT LENGTH AND SOME ANTIOXIDANT ENZYME ACTIVITIES OF TWO DIFFERENT TOMATO SEEDLINGS - H. Basak; K. Demir; Z. B. Doganlar (Journal of Animal and Plant Sciences, 2012)
In this study, we determined the changes in root-shoot length, chlorophyll and carotenoid contents, and some antioxidant enzyme activities in leaf tissues of two different tomato (Lycopersicon esculentum Mill. cv. Aspendos and Donna) seedlings exposed to exogenous abscisic acid (ABA) 7 day intervals for a period of 28 days. Tomato seedlings were grown under controlled conditions using at seedling industry. When the seedlings had first true leaves, ABA was sprayed at 1, 10, 50 and 100 µM on upper and lower epidermis of plants. While 1 and 10 µM ABA exposure caused increases, 50 and 100 µM ABA exposure caused decreases in root and stem length of both tomato cultivars compared to control. Treatment with all ABA concentrations significantly increased the activities of superoxide dismutase (SOD, E.C. 1.15.1.1), catalase (CAT, E.C. 1.11.1.6) and peroxidase (POD, E.C. 1.11.1.7) enzymes. Root-shoot length and pigment content were positively affected by ABA application for 14 and 21 days but 28 days application caused reductions in both parameters. Results of this study revealed that application of ABA at 1 or 10 µM for 14-21 day have shown beneficial role for tomato seedlings. Additionally, we thought that these seedlings which have higher chlorophyll content and SOD, POD and CAT activity compared to controls, were more resistant against various environmental stresses.
Keywords: Abscisid acid; pigments; antioxidant enzymes; Lycopersicon esculentum Mill